Arnold's Projective Plane and r-Matrices. (6th April 2010) - Uchino, K.
Abstract : We will explain Arnold's 2-dimensional (shortly, 2D) projective geometry (Arnold, 2005) by means of lattice theory. It will be shown that the projection of the set of nontrivial triangularr -matrices is the pencil of tangent lines of a quadratic curve on Arnold's projective plane.